The wheel of time: How abstract concepts emerge: (a study based on early Sanskrit texts) - Jurewicz, Joanna (Public Journal of Semiotics, 2019)
<p class="TreA" style="text-align: justify; text-justify: inter-ideograph; tab-stops: 35.4pt 70.8pt 106.2pt 141.6pt 6.0cm 177.0pt 212.4pt 247.8pt 283.2pt 318.6pt 354.0pt 389.4pt 399.9pt 399.9pt; margin: 0cm 6.7pt 10.0pt 7.1pt;">The aim of the paper is to show how conceptual metonymy, metaphor and blending, as discussed in cognitive linguistics, can be used in the investigation on the beginning of abstraction in philosophical thinking. The analysis is based on selected stanzas from the Ṛgveda (ca. 13th BC), the Atharvaveda (ca. 10-9th BC) and the Mahābhārata (ca. 4th BC - 4th AD) composed in Sanskrit. I discuss how the notion of riding in a chariot, used in the earliest texts for expressing ontological, epistemological and ritual issues, is transformed into an abstract concept of the wheel to express the concept of time. The use of cognitive models allows showing the conscious and rational nature of this transformation performed by the early Indian thinkers, and thus qualifies as a form of philosophy.